2016
DOI: 10.1089/end.2016.0496
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Nephrolithotomy in Immunocompromised Patients: Outcomes from a Matched Case–Control Study

Abstract: Immunocompromised patients are at higher risk for complications such as bleeding after PCNL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…[ 7 ] reported 13 management modalities for ureteral stent calcification: eight that involved bladder lithotripsy, ureteroscopy (URS), and retrograde intrarenal surgery (RIRS), two that involved URS and extracorporeal shock wave lithotripsy (ESWL), two that involved bladder stone, URS, RIRS, and ESWL. According to Torricelli FC's report [ 8 ], there was a considerably higher chance of bleeding in HIV patients who underwent percutaneous nephrolithotomy for upper urinary tract stones. This encompasses not just the patient's danger, but also the risk to the health care practitioner.…”
Section: Discussionmentioning
confidence: 99%
“…[ 7 ] reported 13 management modalities for ureteral stent calcification: eight that involved bladder lithotripsy, ureteroscopy (URS), and retrograde intrarenal surgery (RIRS), two that involved URS and extracorporeal shock wave lithotripsy (ESWL), two that involved bladder stone, URS, RIRS, and ESWL. According to Torricelli FC's report [ 8 ], there was a considerably higher chance of bleeding in HIV patients who underwent percutaneous nephrolithotomy for upper urinary tract stones. This encompasses not just the patient's danger, but also the risk to the health care practitioner.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of upper urinary tract stones smaller than 2 cm with flexible ureteroscopic lithotripsy is considered the criterion standard [ 1 ]. Torricelli et al [ 2 ] reported that treatment of upper urinary tract stones in HIV-positive patients with percutaneous nephrolithotripsy is associated with an increased risk of complications compared with this treatment in ordinary patients, including a significantly increased risk of bleeding. This entails not only risk to the patient but also to the health care workers.…”
Section: Discussionmentioning
confidence: 99%